2011
DOI: 10.1111/j.1399-0004.2011.01732.x
|View full text |Cite
|
Sign up to set email alerts
|

Population‐specific spectrum of the F11 mutations in Koreans: evidence for a founder effect

Abstract: The aim of this study was to investigate a mutation spectrum of F11 among Korean patients with factor XI (FXI) deficiency and to determine the haplotypes of mutations frequently found in Koreans. Thirteen unrelated patients from non-consanguineous families with FXI deficiency were included in the study. In the mutation analysis, the most frequently found mutations were Q263X (four cases; 31%) and Q226X (three cases; 23%). The frequency of Q263X-bearing haplotype was significantly different between normal and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…Only 17 cases of FXI deficiency (including the present case) have been confirmed by molecular and genetic testing in Korea [14, 16, 17, 18] (Table 1). Therefore, further testing and discovery of molecular lesions in the F11 gene in the Korean patients with FXI deficiency is needed to gain better understanding of founder mutations that are specific to this population.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…Only 17 cases of FXI deficiency (including the present case) have been confirmed by molecular and genetic testing in Korea [14, 16, 17, 18] (Table 1). Therefore, further testing and discovery of molecular lesions in the F11 gene in the Korean patients with FXI deficiency is needed to gain better understanding of founder mutations that are specific to this population.…”
mentioning
confidence: 89%
“…The fact that some mutations, such as F283L and E117X, predominate in one population (i.e., the Ashkenazi Jewish population) but have never been found in others (i.e., Asian populations) indicates that they are likely to be founder mutations. Although large-scale population studies have not been carried out in a specific Asian population, smaller-scale studies have shown the prevalence of two nonsense mutations (Q226X and Q263X) in Japanese [12], Chinese [13], and Korean [14] patients. In this letter, we report the first case of a heterozygous mutation (C482W) in the F11 gene, resulting in a mild FXI deficiency in a Korean patient.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The five other synonymous variants (rs5973, rs5974, rs5970, rs5971 and rs5976) have been extensively used as markers for haplotype analysis (Bolton-Maggs et al 2004;Quelin et al 2004;Zadra et al 2004;Zadra et al 2008;Kim et al 2012;Bicocchi et al 2013), which is not surprising as three (rs5973, rs5974 and rs5970) are in marked linkage disequilibrium with one another (Tarumi et al 2000). These three neutral variants were initially reported by Martincic et al (1998).…”
Section: Synonymous Variantsmentioning
confidence: 99%
“…Furthermore, rs2289252 was associated with miscarriages, decreased APTT and high FXI levels. (Ventura et al 2000;Zivelin et al 2002;Zadra et al 2004;Zadra et al 2008;Kim et al 2012;Bicocchi et al 2013) rs5970 c.1191T > C p.Gly397¼ Exon 11 VTE N (Gerdes et al 2004) N (Zivelin et al 2002;de Moerloose et al 2004;Zadra et al 2004;Bezak et al 2005;Jayandharan et al 2005;Zadra et al 2008;Kim et al 2012;Bicocchi et al 2013), (Martincic et al 1998) This SNV is located in intron 12 (c.1481-188) and the result of a C > T substitution. Eight other SNVs, including rs1593, rs3822057, rs925451, rs4253430, rs4253414, rs4253399, rs3733403 and rs3822056 also showed an association with venous thrombosis.…”
Section: Non-coding Variantsmentioning
confidence: 99%